PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DI INDONESIA TERHADAP PELAKU KORPORASI (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2019)
Law enforcement in Indonesia in the case of Corruption Crimes outlined in Transparency International (IT) data Indonesia is still considered the most corrupt. Such conditions require the handling of criminal acts that are